Composición Y Estructura De La Herpetofauna En Dos Agro ecosistemas Con Manejo Agrícola Diferente En Quimbaya, Quindío (2015)
There are many factors contributing to declines in natural populations, such as transforming the rainforest into more homogeneous sites, due to the many forms of land management, generating fragmentation of the landscape, being the monocultures predominant agricultural practices. The continuous changes of land use affect all biological diversity. In this study we compared two types of productive agro-ecosystems (Traditional Agroecosystem vs. Polyculture) which have different agricultural practices, with the purpose of identifying variables that affect the presence of the amphibian and reptile’s species, through VES transect method and free survey, along eight samplings in each site, from May to September 2014. The richness and diversity analysis showed that there are significant differences between agro-ecosystems, being Polyculture 2.6 times richer corresponding to a sample coverage of 94.1% which was 1.8 times more diverse (1D) than the Traditional. This could be because the Agroecosystem Polyculture has a more complex horizontally and vertically structure, creating diverse environments with optimal conditions for the development of amphibians and reptiles, that prefer to inhabit areas with dense vegetation near bodies of water. These entire highlights the importance of Agroecosystems for herpetofauna sustainability within an agricultural matrix, hence the significance of knowing and divulgate them as part of the coffee cultural landscape.